Maori Health, Colonization and Post-Colonization: Aotearoa New Zealand, from 1769 - Pool, Ian (Umeå University Library, 2017)
The Māori of Aotearoa New Zealand are a case-study of the negative impacts of colonization on the health of precursor peoples, such as indigenous peoples in Australia, the Americas, and northern Eurasia. But, colonization has such effects regardless of whether colonized peoples eventually become “independent,” or are swamped demographically and politically by a settler population. Indigenous peoples still suffer “internal colonialism” after their country becomes independent (from the United Kingdom for Aotearoa), even in social democracies, simply because majorities, through benign neglect or paternalism, often fail to meet the particular needs of indigenous citizens. Incidentally, “independent” ex-colonies do not escape post-colonialism, because they are subject to interventions by powerful international and bi-lateral agencies, such as structural adjustment policies imposed by the World Bank. This paper uses the epidemiological transition framework, but questions its application to colonized peoples, who often, contrary to the paradigm’s deterministic principle of progress, may suffer “regression” as their very survival is threatened by newly introduced diseases to which they have no immunity. Some, not Māori, even go through demographic collapses.” The eventual Māori transition did follow the conventional framework, but in its “delayed” form. Finally the paper shifts from theoretical dimensions into praxis: health services. It identifies stages in the evolution of these as they affect indigenous people. This is a more detailed overview than the conventional view: a shift from social determinants of health change to the impacts of public health interventions, and from the domination of communicable diseases to non-communicable.